Desomorphine (Krokodil): An overview of its chemistry, pharmacology, metabolism, toxicology and analysis. (1st April 2017) - Florez, Diego Hernando Ângulo; dos Santos Moreira, Ana Maria; da Silva, Pedro Rafael; Brandão, Ricardo; Borges, Marcella Matos Cordeiro; de Santana, Fernando José Malagueño; Borges, Keyller Bastos
Graphical abstract: Krokodil (as is known by the street) is an opioid denominated desomorphine. This injectable semi-synthetic opioid drug has been largely used in the last years for recreational purposes in Russia and several European and American countries. It is time for society around the world open their eyes to this old dangerous drug. Highlights: A review about all key points about desomorphine was proposed. Frequently new cases of "Krokodil" abuse around the world has been detected. Analytical approaches for desomorphine determination were reviewed. New analytical methods for desomorphine, contaminants and metabolites are required. Abstract: Background: "Krokodil" or "Crocodile" is an illegal homemade desomorphine drug obtained from chemical reactions of commercial codeine drugs with several other powerful and highly toxic chemical agents increasing its addiction and hallucinogenic effects when compared with other morphine analogues. Methods: This paper summarizes a complete review about an old drug called desomorphine (Krokodil), presenting its chemistry, pharmacology, metabolism, toxicology and analysis. Results: It is of particular interest and concern because this cheaper injectable semisynthetic opioid drug has been largely used in recent years for recreational purposes in several Eastern European as well as North and South American countries, despite known damage to health that continuous use might induce. These injuries are much stronger and more aggressive than morphine's, infecting and rotting skin and soft tissue to the bone of addicts at the point of injection in less than three years, which, in most cases, evolves to death. On this basis, it is imperative that literature reviews focus on the chemistry, pharmacology, toxicology and analysis of dangerous Krokodil to find strategies for rapid and effective determination to mitigate its adverse effects on addicts and prevent consumption. Conclusions: It is crucial to know the symptoms and consequences of the use of Krokodil, as well as Methods: for identification and quantification of desomorphine, contaminants and metabolites, which can help the forensic work of diagnosis and propose actions to control and eradicate this great danger to public health around the world.